Rice productivity and profitability in Myanmar: Assessment of the 2023 monsoon - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2024)
We have analyzed rice productivity and profitability data for the 2023 monsoon season from the Myanmar Agriculture Performance Survey (MAPS), conducted at the beginning of 2024. This survey encompassed plots managed by 2,840 rice producers, distributed across all states/regions of the country. Our findings reveal: 1. National rice productivity exhibited an average increase of 7 percent during the 2023 monsoon compared to the previous year, reversing the decline witnessed in the 2022 monsoon. This year's heightened productivity primarily stems from increased input usage (particularly fertilizer), greater labor inputs (with more farmers adopting transplanting), and reduced occurrences of natural shocks, notably droughts. 2. The Ayeyarwady region, the country's principal rice-producing area, experienced an 11 percent increase in rice productivity. Conversely, rice yields remained low in Kayah and Chin, two states affected by severe conflict. The highest yields, along with notable increases over the past three years, are observed in Nay Pyi Taw. 3. Significant changes in input costs for rice cultivation were observed between the two seasons: 3.1 Prices of urea, the most important chemical fertilizer used by rice farmers, decreased by 16 percent. 3.2 Mechanization costs surged by a notable 42 percent, which is concerning, especially in light of escalating rural labor scarcity. Particularly pronounced increases in mechanization costs were noted in coastal areas where fuel prices were high, or fuel was not available at all. 4. Substantial changes in technology adoption and input utilization compared to the previous monsoon were noted: 4.1 Fertilizer use on rice increased by 20 percent. 4.2 Use of self-preserved seed – instead of obtaining it from the market - increased by 6 percentage points compared to last monsoon, and 17 percentage points compared to 2020. 4.3 Transplanting increased by 5 percentage points while broadcasting declined by 7 percentage points. 4.4 The use of combine harvesters on rice was 1 percentage point lower compared to last year but was 12 percentage points lower than in 2020. 5. Thirty percent of paddy farmers reported being impacted by climatic or other production shocks during this monsoon, with floods (reported by seven percent of farmers) and droughts (reported by five percent) having significant adverse effects on yields. When affected, paddy yields decreased by 32 and 51 percent, respectively. Incidences of pests, diseases, and weeds have the highest frequency overall (13 percent). 6. Substantial changes in input usage and technology adoption were observed in paddy cultivation within coastal areas (Rakhine and Tanintharyi), seemingly linked to insecurity, mobility constraints, and fuel accessibility issues: 6.1 Fertilizer use declined by one-third. 6.2 The utilization of combine harvesters plummeted by 26 percentage points. 7. Paddy prices at the farm level surged by 64 percent, reflecting changes in international rice prices as well as the depreciation of the MMK. 8. Real – in terms of the cost of an average food basket – profits from rice farming during the monsoon of 2023 increased by 43 percent compared to the previous year. While nominal profits doubled since the previous monsoon, high price inflation tempered the increase in real profits. 9. The paddy sector has proven resilient in 2023, with improved pricing incentivizing farmers to intensify production through increased usage of chemical fertilizers and labor inputs.